ANALISIS KORELASI ANTARA INTENSITAS PELAKSANAAN SHOLAT DHUHA BERJAMAAH DENGAN TINGKAT KARAKTER GOTONG ROYONG SISWA - Alfiyani, Nur; Faza, Muhammad Kamal; Hosna, Rofiatul (Raudhah - Proud To Be Professional, 2025)
This study aims to analyze the correlation between the intensity of congregational Dhuha Prayer implementation and the level of gotong royong (mutual cooperation) character among 3rd grade students of MI Thoriqul Huda in the context of Merdeka Curriculum implementation and Pancasila Student Profile development. Using a correlational quantitative approach, the research involved 25 third-grade students selected through total sampling. Data collection was conducted through structured observation to measure the intensity of congregational Dhuha Prayer implementation over 8 weeks, questionnaires to measure gotong royong character, documentation, and semi-structured interviews as supporting data. The results showed a very strong and significant positive relationship between the intensity of congregational Dhuha Prayer implementation and students' gotong royong character level. The intensity of congregational Dhuha Prayer implementation contributed 97.2% to students' gotong royong character level. Further analysis found that the cooperation ability indicator had the highest correlation, while conflict resolution ability had the lowest. This research provides empirical evidence that the habitual congregational Dhuha Prayer program can be an effective means of developing gotong royong character according to the Pancasila Student Profile dimensions and demonstrates the potential integration of Islamic values with national character education in Merdeka Curriculum implementation.